BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Practical Plant Virology - Protocols and Exercises J. Dijkstra and CP. de Jager. Springer, Berlin, 459 pp.Fungicides in Crop Protection, H,G, Hewitt, CABÂ International, 1998, 221 pp.